Edukasi Kepada Ibu Hamil Tentang Deteksi Dini Tumbuh Kembang Anak Dengan Apgar Score di Komunitas Ibu Hamil Puskesmas Gajahan Surakarta - Nurul Fikri Mufidah; Adnan Faris Naufal; Amalia Faradilla Rahim (OBAT: Jurnal Riset Ilmu Farmasi dan Kesehatan, 2024)
Apgar is an examination of newborns with five aspects of assessment, namely skin color, heart rate, reflex response, active muscle tone and breathing. Early detection with assessment is very important for health and the growth and development process. A low Apgar score can indicate immunological abnormalities in the neonate such as respiratory, heart and neurological problems as well as a risk of neonatal sepsis. There is still little information on the Apgar assessment given to pregnant women. The partner of this service activity is the Pregnant Women's Community at Gajahan Surakarta Health Center. The aim of this outreach activity is to provide a forum for information to pregnant women at the Gajahan Surakarta Community Health Center about the Apgar assessment and determine the level of understanding of this education. A baby is said to be healthy if it has an Apgar score of more than seven. The educational method provided is through the lecture method, distributing leaflets about the Apgar score. To measure the level of understanding and knowledge, a pre-test was carried out before delivering the material and a post-test after being given education. Based on the results of the pre-test and post-test comparison of 27 respondents, the average score increased from 77.7 to 91. Participants were enthusiastic in taking part in this activity and there was an increase in pregnant women's understanding of the Apgar score